Stepsister scheme - Hines, Jim C. (New York DAW Books, 2009)
"You know how all those old fairy tales take you through lots of scary adventures till you finally reach that inevitable line: 'And they all lived happily ever after--' Guess what? It's not true. Life in never-never land isn't all sweetness and light. Cinderella--whose real name is Danielle Whiteshore (nee Danielle de Glas)--does marry Prince Armand. And their wedding is a dream come true. But not long after the 'happily ever after, ' Danielle is attacked by her stepsister Charlotte, who suddenly has all sorts of magic to call upon. And though Talia--otherwise known as Sleeping Beauty--comes to the rescue (she's a martial arts master, and all those fairy blessings make her almost unbeatable), Charlotte gets away."--Page 4 of cover.
105560
Keywords: Cinderella -- (Legendary character) -- Fiction; Cinderella -- (Legendary character); Fairy tales -- Fiction; Kidnapping; Stepsisters; Young adults; Fantasy fiction; Young adults -- Fiction; Humorous stories